2017
DOI: 10.1503/cmaj.160823
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in ambulatory care and incidence of cardiovascular events

Abstract: BACKGROUND: Variations in the prevalence of traditional cardiac risk factors only partially account for geographic variations in the incidence of cardiovascular disease. We examined the extent to which preventive ambulatory health care services contribute to geographic variations in cardiovascular event rates. METHODS:We conducted a cohort study involving 5.5 million patients aged 40 to 79 years in Ontario, Canada, with no hospital stays for cardiovascular disease as of January 2008, through linkage of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Use of the set of quality indicators developed by the CANHEART initiative (based on previous versions of the C-CHANGE guideline) has shown that health regions in Ontario with better adherence to these guidelines have fewer cardiovascular events. 92,93 The Triple Aim Framework offers a foundation for health care providers to conceptualize health care with an emphasis on optimizing health for individuals and populations, and the health care experience. 94 This framework considers the patient experience of care, health of populations and per capita cost of health care, all of which need to be considered simultaneously.…”
Section: Health Behavioursmentioning
confidence: 99%
“…Use of the set of quality indicators developed by the CANHEART initiative (based on previous versions of the C-CHANGE guideline) has shown that health regions in Ontario with better adherence to these guidelines have fewer cardiovascular events. 92,93 The Triple Aim Framework offers a foundation for health care providers to conceptualize health care with an emphasis on optimizing health for individuals and populations, and the health care experience. 94 This framework considers the patient experience of care, health of populations and per capita cost of health care, all of which need to be considered simultaneously.…”
Section: Health Behavioursmentioning
confidence: 99%
“…In cancer, for example, the Canadian Strategy for Cancer Control estimated that cancer outcomes in Canada could improve by as much as 30% by appropriately and routinely applying existing scientific evidence in practice (Canadian Strategy for Cancer Control, ). Ultimately, the poor uptake of evidence means that many patients do not benefit from optimal care (Curtis, Walker, & Goldacre, ; Kryworuchko, Stacey, Bai, & Graham, ; Sheldon et al., ; Tu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…early childhood development, and link them with other health data including electronic medical records 8 and cancer and perinatal registries. For example, by linking 17 sources of data, Ontario researchers assessed regional variation in cardiovascular event rates 9 and the added value of highintensity statin therapy for older patients. 10 A crucial advantage of these "real-world" data is their coverage of Canadians of all ages and ethnicities.…”
mentioning
confidence: 99%